Nuclear receptors: emerging drug targets for parasitic diseases - Wang, Zhu (J Clin Invest, 2017)
Parasitic worms infect billions of people worldwide. Current treatments rely on a small group of drugs that have been used for decades. A shortcoming of these drugs is their inability to target the intractable infectious stage of the parasite. As well-known therapeutic targets in mammals, nuclear receptors have begun to be studied in parasitic worms, where they are widely distributed and play key roles in governing metabolic and developmental transcriptional networks. One such nuclear receptor is DAF-12, which is required for normal nematode development, including the all-important infectious stage. Here we review the emerging literature that implicates DAF-12 and potentially other nuclear receptors as novel anthelmintic targets.